Pengaruh Pemberian Antibiotik Profilaksis Sefazolin, Seftriakson dan Antibiotik Seftriakson Sebelum dan Sesudah Operasi Terhadap Infeksi Luka Pasca Operasi - Herti Marni; Dovy Djanas; Hafni Bachtiar (Universitas Andalas, 2020)
Objective : To determine the effect of giving prophylactic antibiotic ceftriaxone and cefazolin and giving ceftriaxone before and after surgery to the risk of postoperative wound infection in postoperative patients.Method: This study was an experimental study with a post test control group design that looked at the differences in the effect of administration of ceftriaxone, cefazolin, and ceftriaxone before and after surgery on the risk of postoperative wound infection. The population in this study were patients planned for surgery in the Obstetric and Gynelologic Departement of Dr. M. Djamil General Hopital, Padang. The number of samples used by 30 people with a group of 10 people each group. The study began in August until the number of samples was fulfilled. Univariate analysis was used to see the frequency, percentage, mean, and standard deviation. Bivariate analysis using Chi-square test with 95% CI (α <0.05) was used to see differences in the effect of the three antibiotic procedures.Results: There were no cases of postoperative wound infection based on the three procedures used. There was no difference in the effect of prophylactic antibiotics in postoperative infections. Conclusion: There was no difference in the effect of the three procedures for prophylactic antibiotics in postoperative infections.Keywords: Prophylactic Antibiotics, Surgical Wound Infections, Cefazolin, Ceftriaxone, Superficial incisional SSI